Sharia-Based Human Development in Realizing Equitable Welfare in Banten Province - Prima Dwi Priyatno; Fitri Yetti; Sasmita Nurvinda Laili (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Although economic growth is often used as a development benchmark, a holistic assessment of quality of life requires more comprehensive indicators. This study analyzes human development across eight regencies/cities in Banten Province using a maqashid syariah approach. Employing a quantitative descriptive method with composite index construction, the research develops an Islamic Human Development Index (IHDI) based on five dimensions: safeguarding religion (hifdz al-dīn), life (hifdz al-nafs), intellect (hifdz al-‘aql), progeny (hifdz al-nasl), and wealth (hifdz al-māl). Secondary data were normalized and aggregated using weighted calculations. The results reveal substantial regional disparities, with Cilegon City recording the highest IHDI (0.69546) and Lebak Regency the lowest (0.48958). These gaps are mainly driven by the intellect and wealth dimensions, which remain weaker in agrarian regions than in urban areas. Despite a zero score in the religion dimension, Tangerang City maintains a moderate IHDI due to strong performance in intellect and wealth. The findings highlight the importance of integrating maqashid syariah into equitable regional development policies, particularly through improving education and strengthening local economies.